Ethnobotanical Survey on Bitter Tea in Taiwan - Chao, Jung; Chen, Ting-Yang; Pao, Li-Heng; Deng, Jeng-Shyan; Cheng, Yung-Chi; Su, Shan-Yu; Huang, Shyh-Shyun (Frontiers in Pharmacology, 2022)
Ethnopharmacological evidence. In Taiwan, herbal tea is considered a traditional medicine and has been consumed for hundreds of years. In contrast to regular tea, herbal teas are prepared using plants other than the regular tea plant, Camellia sinensis (L.) Kuntze. Bitter tea (kǔ-chá), a series of herbal teas prepared in response to common diseases in Taiwan, is often made from local Taiwanese plants. However, the raw materials and formulations have been kept secret and verbally passed down by store owners across generations without a fixed recipe, and the constituent plant materials have not been disclosed. Aim of the study. The aim was to determine the herbal composition of bitter tea sold in Taiwan, which can facilitate further studies on pharmacological applications and conserve cultural resources. Materials and methods. Interviews were conducted through a semi-structured questionnaire. The surveyed respondents were traditional sellers of traditional herbal tea. Subsequently, the relevant literature was collated for a systematic analysis of the composition, characteristics, and traditional and modern applications of the plant materials used in bitter tea. We also conducted an association analysis of the composition of Taiwanese bitter tea with green herb tea (qing-cao-cha tea), another commonly consumed herbal tea in Taiwan, as well as herbal teas in neighboring areas outside Taiwan. Results. After visiting a total of 59 stores, we identified 32 bitter tea formulations and 73 plant materials. Compositae was the most commonly used family, and most stores used whole plants. According to a network analysis of nine plant materials used in high frequency as drug pairs, Tithonia diversifolia and Ajuga nipponensis were found to be the core plant materials used in Taiwanese bitter tea. Conclusions. Based on the results, plant materials used in Taiwanese bitter tea were distinct, with multiple therapeutic functions. Further research is required to clarify their efficacy and mechanisms.